Sistem pengurusan penyenggaraan bangunan bagi struktur konkrit bertetulang - Mohd. Ariffin, Mohd. Azreen (2006)
A building is an asset which needs to be maintained to ensure that its value is not eroded. Lack of maintenance will result in unfortunate economic and safety consequences. The objectives of this study are to study the maintenance management system for reinforced concrete structures of the buildings and to propose an efficient management system that could be adopted by the owner. Five (5) organizations in Kelantan were chosen to represent the old and new buildings, government and public sector. Data were collected through visits to respected sites and interviews with the involved personnel. Cracking of internal and external elements are studied in this projects